The use of a calibrated three phase (solid-aqueous-gas) plant-wide wastewater treatment model to simulate data on mineral precipitation - Ponco, Linamandla (Department of Civil Engineering, 2025)
The mass manufacture of novel chemicals, extensive use, and the release of micropollutants into the environment are inevitable occurrences in contemporary society. In reality, wastewater treatment plants are the primary means of spreading micropollutants, primarily because of their inadequate performance. However, efforts are being made to improve their efficiency and achieve an 80% reduction in micropollutant levels. Among the several methods used for the tertiary treatment of wastewater, adsorption stands out for its effectiveness in removing micropollutants. One popular adsorption material is activated carbon, however, the most common commercial version is expensive and made from coal, which is a scarce resource. As a result, we must immediately begin investigating potential substitute precursors that can produce effective activated carbon and are both easily accessible and inexpensive. Because of its high organic content, sludge from wastewater treatment plants is showing promise as an alternative. Stricter disposal restrictions make it more difficult to manage this sludge, a by-product of water treatment. Subsequently, the two varieties of carbon were employed in batch adsorption tests to determine the ideal conditions necessary for each carbon to attain the maximum removal of lead (II) ions from aqueous solutions. This entailed manipulating factors such as pH, adsorbent dosage, initial concentration of the adsorbate solution, and contact time. The optimum conditions that were obtained were 180 min contact time, 300 mg adsorbent dose, and pH of 8. Comparing the results obtained from these tests under optimal conditions for each adsorbent, it was determined that the percentage removal of lead (II) ions was as follows: GAC (99.91%) > HC-PS-WAS-Scr (97.25%), indicating that GAC exhibited a marginally superior performance in the removal of the pollutants compared to the other adsorbents. Adsorption behaviour could be described using the Langmuir and Freundlich isotherm model. Regardless of the adsorbent studied, Langmuir isotherm model fitted well with the adsorption data. The maximum adsorption capacity was found to be 66 mg/g for HC-PS-WAS and 60 mg/g for GAC. The adsorption kinetics could most likely be described with pseudo second order kinetic model for both adsorbents considered.